Respostas barorreflexa e autonômica a dois protocolos isométricos equalizados em densidade - Mello, Igor Alves (2021)
Introduction: Baroreflex is one of the blood pressure control mechanisms affected by autonomic modulation and is responsable for attenuating abrupt changes in blood pressure. Both raise and decay of blood pressure levels cause structural changes on baroreceptors, changing its afferent firing frequency, thus adjusting blood pressure levels. Significant reductions in baroreflex sensitivity following dynamic resistance exercise have been reported, in a set configuration-dependant manner. As for isometric exercise, little has been documented about the influence of work-to-rest ratio on baroreflex responses. Aim: to investigate the autonomic and baroreflex responses to two isometric protocols with same intensity and work-to-rest ratio in young normotensive women. Materials and methods: 11 normotensive females (25 ± 3 years, height: 1.63 ± 0.07 meters, body mass: 60.7 ± 6.0 kg, body mass index (BMI): 22.7 ± 1.3 kg/m2, systolic blood pressure (SBP): 112 ± 10 mmHg, diastolic blood pressure (DBP): 71 ± 5 mmHg, heart rate (HR): 73 ± 11 bpm, one repetition maximum (1RM): 249 ± 62kg) performed two isometric protocols equalized in W:R on different days and random order. Protocol A: 4 sets x 2 min isometric x 2 min intervals. Protocol B: 16 sets x 30 sec isometric x 24 sec interval between sets. The standardized load was 30% 1-RM (75 ± 19kg) for both protocols. The protocols had the same total time under tension (480s), total rest (360s), and total sustained weight (30% 1-RM). Hemodynamic and autonomic variables were continuously monitored by photoplestimography. Results: both protocols caused significant reduction in baroreflex gain (Up Gain, Down Gain & All Gain), Up BEI and All BEI compared to rest (p<0,05), WHEREas Protocol A gain reduction lasted longer. No differences were found for Down BEI (p>0,05). Mean BP and LF (mmHg2) augmented significantly during exercise (p<0,05), with no differences comparing pre and all post exercise values (p>0,05). R-R intervals were reduced in both protocols, remaining lower than pre values until immediate end of exercise in Protocol B (p<0,05) and up to 60 minutes after exercise in Protocol A (p<0,05). Only Protocol B showed significant RMSSD reduction, which was lower during exercise compared to pre values (p<0,05). SDNN was augmented during exercise in Protocol A (p<0,05), with no significant changes in Protocol B (p>0,05). HF (ms2) values were reduced only in Protocol B during exercise (p<0,05), while LF/HF ratio was augmented also only in Protocol B during exercise (p<0,05). None of the protocols showed significant differences for LF (ms2) at any moment (p>0,05). Conclusion: Protocol A caused longer reductions in baroreflex gain, while Protocol B caused greater disturbance in autonomic indexes of heart rate variability. These findings suggest that different isometric set configurations equated in work-to-rest ratio may lead to distinct baroreflex and autonomic responses.